Analisis Normatif Atas Keterbatasan Pengaturan OJK Terkait Perlindungan Nasabah dalam Menghadapi Ancaman Risiko Social Engineering - Mika Anwarita Pakpahan; Yuniar Pamadya Astuti (PT PUSTAKA CENDEKIA GROUP, 2025)
This article analyzes the effectiveness of customer protection regulations in digital banking services against the threat of social engineering, a form of modern financial risk. This research uses normative legal methods by examining regulations, legal literature, and empirical research findings related to digital crime in the banking sector. The results show that although the regulatory framework addresses the principles of consumer protection, system security, and risk management, these regulations do not specifically address the complexity of social engineering, which is rooted in psychological manipulation and low customer digital literacy. The absence of investigative standards, limits of liability, and independent evidentiary mechanisms leaves customers in a very vulnerable position when funds are lost. This article concludes that more detailed and adaptive regulatory updates are needed, including a strengthened accountability model, transparent investigation procedures, and increased digital security education to strengthen legal protection for customers in the digital banking ecosystem.